2020
DOI: 10.1113/ep088103
|View full text |Cite
|
Sign up to set email alerts
|

The hyperpnoea of exercise in health: Respiratory influences on neurovascular control

Abstract: It is known that the respiratory muscles have a significant increasing oxygen demand in line with hyperpnoea during whole-body endurance exercise and are susceptible to fatigue, in much the same way as locomotor muscles. The act of ventilation can itself be considered a form of exercise. The manipulation of respiratory load at near-maximal exercise alters leg blood flow significantly, demonstrating a competitive relationship between different skeletal muscle vascular beds to perfuse both sets of muscles adequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The intercostals, parasternals, scalenes, and neck muscles contribute to ventilation at high intensities by moderating EILV and airway caliber (e.g., dilation and inflammation). Altogether, the diaphragm and associated ventilatory pump musculature are remarkably efficient [~3%–5% total O 2 consumption (VO 2 )] and fatigue-resistant at submaximal intensities ( Welch et al, 2019 ; Sheel et al, 2020 ).…”
Section: Respiration During Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…The intercostals, parasternals, scalenes, and neck muscles contribute to ventilation at high intensities by moderating EILV and airway caliber (e.g., dilation and inflammation). Altogether, the diaphragm and associated ventilatory pump musculature are remarkably efficient [~3%–5% total O 2 consumption (VO 2 )] and fatigue-resistant at submaximal intensities ( Welch et al, 2019 ; Sheel et al, 2020 ).…”
Section: Respiration During Exercisementioning
confidence: 99%
“…Flow limitation could lead to “breath stacking,” a negative consequence when subsequent breaths have slightly larger inspiratory than expiratory flow ( Ward, 2007 ). Breath stacking causes EILV and EELV to progressively increase, leading to dynamic hyperinflation ( Figure 3 ; Sheel et al, 2020 ). At these higher LOV, the lungs are stiffer, less compliant, and require more muscle work to expand ( Sheel et al, 2020 ).…”
Section: Respiration During Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a series of studies revealed increased sympathetic vasomotor outflow and reduced resting limb blood flow in association with respiratory muscle work (Derchak et al, 2002;Sheel et al, 2001Sheel et al, , 2002St Croix et al, 2000). Based on these data, it is obvious that increased work of breathing leads to metabolite accumulation within the respiratory muscle (i.e., respiratory muscle-induced metaboreflex), which affects the distribution of limb blood flow (Dempsey et al, 2006;Sheel et al, 2020).…”
Section: Influence Of Respiratory Muscle-induced Metaboreflex On Coel...mentioning
confidence: 99%
“…In their report, Sheel, Taylor, and Katayama (2020) emphasise recent findings in healthy humans that show a significant influence of sympathetic vasoconstrictor activity, mediated by both respiratory and locomotor muscle metaboreceptors during intense endurance exercise, on the constraint of blood flow and O 2 transport to both sets of muscles. Experimentally increasing the work of breathing was found to elicit reductions in blood flow to inactive and active limb muscles during submaximal exercise, but only if the work of breathing was of a sufficient magnitude.…”
mentioning
confidence: 98%